Disability and inclusion in Kazakhstan. Issue 7 (9th August 2022) - Allan, Julie; Omarova, Tolkyn
Abstract: The Republic of Kazakhstan ratified the United Nations Convention on the Rights of Disabled People in January 2015 as part of a programme of 'Future without Barriers' and has sought to make the majority of its schools inclusive. This paper reports on progress towards inclusion and the challenges faced by a nation that is aspiring to develop as an independent nation whilst still utilising knowledge and capital from the former Soviet Union. An analysis of the country's 'readiness' for inclusive education is offered, using Hacking's 2010 concept of (2006 ; 1998a & b ; 2010 ) 'making up people' and Mitchell's 'ablenationalism'. Ablenationalism is also used to explore how Kazakhstan's efforts to assert its own distinctive identity and culture affected the positioning of disabled children and adults within education and within society. We conclude with some considerations of the possibilities for the future rights of disabled children and for inclusion. Points of interest: This article focuses on the republic of Kazakhstan, which separated from the Soviet Union in 1991. The country has made significant efforts to introduce inclusive education over a short period of time and there has been some success. A major barrier to progress comes from the country's system of assessing and classifying disabled children. Teachers have found inclusive education challenging and many have expressed a preference for segregation. Parents faced enormous challenges in having their disabled children accepted in mainstream schools. However, by establishing parents' groups, they have been able to influence policy and practice and increase progress towards inclusive education. Recommendations made to the Ministry of Education and Science of Kazakhstan, who commissioned this research, included adopting an international perspective to enable it to learn from other countries; incentives to schools to encourage greater inclusiveness and extended media campaigns to change attitudes towards disability.